PILOTSTUDY TO EVALUATE THE EFFECT OF PHOSPHORUSBINDERS ON FGF23 - A.Bouma de Krijger; P.M. ter Wee; F.J. van Ittersum; M.G. Vervloet (The Korean Society of Nephrology, 2012)
The Netherlands Fibroblast growth Factor 23 (FGF23) is independently associated with cardiovasculair outcome. A reduction of dietary phosphorus intake in healthy individuals leads to a decrease of FGF23. Data on the potency of phosphate binders to lower FGF23 in CKD stage 3 are conflicting. We treated 18 normophosphatemic CKD stage 3 patients with a fixed dose of sevelamer-carbonate (Renvela®) 2,4 g powder for suspension, before breakfast and diner. Patients remained on their usual diet. Laboratory data were collected 2 weeks prior to baseline, at start of sevelamer, at week 8 following sevelamer treatment and after a wash-out of 2 weeks. We measured serum phosphorus, PTH, FGF23, estimated GFR (by the MDRD formula) and 24-h urinary phosphate excretion. General Estimated Equation was used to evaluate the effect of phosphorusbinding on 24-h urinary phosphate excretion and on FGF23. patientcharacteristics n 18 Age(year) 54 (46,1-62,2) Sex (m/f) 7 / 11 race (% caucasian) 66 eGFR (ml/min/1.73m2) 41.2 ± 9.6 FGF23 (U/l) 158 (116-216) PTH (pmol/l) 7.5(5,4-41,8) Phosphate (mmol/l) 1.09 ± 0.19 Proteinuria (g/24 h) 0,7 (0,2-1,6) Results are as follows; phosphorus binding by sevelamer significantly lowered urinary phosphate excretion, from a median of 26.25 mmol/24 h to 17.5 mmol/l. Other parameters showed no sgnificant association with urinary phosphate excretion. The serum phosphate was unchanged during treatment. Creatinin clearance was significantly associated with FGF23 (p0.03). FGF23 did not change significant following phosphorus binding therapy. In conclusion; although 8 weeks sevelamer treatment significantly lowered 24 h urinary phosphate excretion, there was no reduction in FGF23 levels in this group of CKD stage 3 patients.